IMPLEMENTASI PERLINDUNGAN DATA PRIBADI PASIEN DALAM LAYANAN TELEMEDICINE DI INDONESIA: ANALISIS REGULASI DAN TANTANGAN PRAKTIS - Gunawan Widjaja; Wagiman; Dyah Ersita Yustanti; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (CV. Adiba Aisha Amira, 2025)
Digital transformation in Indonesia's health sector has accelerated the adoption of telemedicine services as an alternative to remote medical services, especially since the COVID-19 pandemic. Telemedicine provides easy access and efficiency of health services for the community, but at the same time increases challenges related to the protection of patients' personal data stored and processed digitally. This study employs a normative legal method with a literature review to analyse regulations governing the protection of patient personal data in telemedicine services in Indonesia, as well as to identify practical challenges in their implementation in the field. The results of the study indicate that although there is a fairly comprehensive legal basis, such as Law No. 27 of 2022 on Personal Data Protection and various other health sector regulations, implementation at the operational level still faces obstacles. These challenges include weak data security infrastructure, low digital literacy among medical personnel and patients, lack of specific technical guidelines, and limited oversight and enforcement of data protection violations. Collaborative efforts between the government, healthcare providers, and the public are needed to strengthen the personal data protection ecosystem, thereby ensuring safe, inclusive, and trustworthy telemedicine services in Indonesia.